Analysis of Gold as a Potential Inflation Hedge in Case of Pakistan - Attiya Yasmin Javid; Sadaf Zafar (NUST Journal of Social Sciences and Humanities, 2021)
In developing countries such as Pakistan, where the macroeconomic situation remains uncertain and inflationary expectations always linger to a high level, investors stay in search of such cost-effective or profitable investment opportunities that can provide their capital an effective hedge against inflation. The present study empirically tests the status of gold as a potential hedge against inflation in Pakistan by analyzing the relationship of the expected and actual inflation with gold return and its cost of carrying, i.e., the interest rate. The autoregressive moving average (ARMA) with generalized autoregressive conditional heteroscedasticity (GARCH) models is applied to examine the time varying relationship between the variables from January 2001 to December 2015. The results support gold as an effective hedge against inflation in Pakistan; since, the returns on gold investment exceeds its cost of carrying with the view of changing expected inflation.